2013
DOI: 10.3109/10903127.2013.804139
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate and Safe Utilization of Helicopter Emergency Medical Services: A Joint Position Statement with Resource Document

Abstract: This position statement with accompanying resource document is the result of a collaborative effort of a writing group comprised of members of the Air Medical Physician Association (AMPA), the American College of Emergency Physicians (ACEP), the National Association of EMS Physicians (NAEMSP), and the American Academy of Emergency Medicine (AAEM). This document has been jointly approved by the boards of all four organizations. Patients benefit from the appropriate utilization of helicopter emergency medical se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
31
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 40 publications
(30 reference statements)
0
31
0
4
Order By: Relevance
“…A helicopter must shorten the time to delivery of care (whether on the scene by skilled aeromedical crew or in hospital) in order to provide any form of benefit to the patient. [2] When comparing the mean on-scene times of both the Netcare 911 HEMS operations with other similarly staffed operations, the mean on-scene times for the Netcare operations were often shorter. [7,20,21] An interesting finding was the similarity between the interfacility transfer and primary transfer on-scene times.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A helicopter must shorten the time to delivery of care (whether on the scene by skilled aeromedical crew or in hospital) in order to provide any form of benefit to the patient. [2] When comparing the mean on-scene times of both the Netcare 911 HEMS operations with other similarly staffed operations, the mean on-scene times for the Netcare operations were often shorter. [7,20,21] An interesting finding was the similarity between the interfacility transfer and primary transfer on-scene times.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the time-sensitive pathologies identified in previous studies were traumatic haemorrhage, ST-elevation myocardial infarction, polytrauma, traumatic brain injury, burns, stroke and paediatric emergencies. [2,19] Polytrauma patients and patients with neurological injuries also appear to derive considerable benefit from doctor-based prehospital care. [14] There can be no doubt that a helicopter is an effective option for patients who have time-sensitive pathologies and are situated in remote areas some distance away from definitive care, as the speed of the operation allows for optimal patient outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The effect of HEMS is still subject to debate although they have several theoretical advantages, such as bringing advanced medical care and medical competence to the scene, shortening the transport time, providing access to remote areas, and reducing the time elapsed until definitive care is available. [2][3][4] Several outcome studies have found positive associations with increased survival under the care of HEMS, [5][6][7] whereas the opposite effects have also been well documented. 5,8,9 However, many of these studies have been subject to methodological limitations, selection bias, and noncomparable study settings or designs.…”
mentioning
confidence: 94%
“…5 A position paper by several American air medical societies initiated the process of establishing national guidelines to facilitate the beneficial effects of HEMS implementation. 4 The paper stated that clinical benefit could be provided by minimizing the time to definitive care in time-sensitive medical conditions, providing necessary competence and equipment on the scene, and accessing patients who are otherwise inaccessible by other modes of transport. 4 These objectives are consistent with national guidelines in other countries.…”
mentioning
confidence: 99%